Attitudes and Beliefs of Deployed United States Military Medical Personnel about Providing Healthcare for Iraqi Patients. (3rd April 2019) - Peterson, Alan L.; Moore, Brian A.; Lancaster, Cynthia A.; Isler, William C.; Baker, Monty T.; McNally, Richard J.; Mintz, Jim; Joseph, Jeremy S.; Moring, John C.; Cedillos, Elizabeth M.; Williams Christians, Iman; Litz, Brett T.
Abstract: This study surveyed 1, 129 U.S. military medical personnel deployed to a combat support hospital in Iraq regarding their attitudes and beliefs about providing healthcare to Iraqi National Guard, civilian, and security detainee patients. A significant percentage of military medical personnel reported they were comfortable treating Iraqi patients. However, a notable proportion indicated discomfort in this role, especially when interacting with security detainees. Nearly half of the medical personnel did not feel adequately prepared or trained for this role. U.S. military medical personnel may benefit from enhanced predeployment cultural education and training tailored to care for the local civilian patient population.